Is Happiness Infectious? - Knight, J; Gunatilaka, R (Department of Economics (University of Oxford), 2009)
The paper uses an appropriate survey from rural China to answer the question: Is happiness infectious, i.e. does the happiness of an individual depend positively on the happiness of their reference group? The evidence is consistent with this hypothesis, but the challenge is to solve the ‘reflection problem’, i.e. is the apparent effect of neighbours’ happiness on own happiness a causal one or merely a reflection? A ‘quasi-panel’ approach is adopted, treating villages as groups and individuals as multiple observations within each group, and using an error components 2SLS estimator. The results suggest that a major part of the relationship is indeed causal: Adam Smith’s insight was correct! The normative and policy implications are briefly considered.